Evaluation of teachers' knowledge of the objectives of the Nigerian integrated science programme and implementation strategies: implications for pedagogical practices (2006)
The study which is essentially exploratory, investigated integrated science teachers' knowledge of the objectives and implimentation strategies of the Nigerian integrated science curriculum. Fifty two teachers randomly drawn from the schools within eight educational zones in Oyo state were involved. The result showed that teachers have the knowledge of the objectives of the programme. The implementation strategies also employed are purely lecture and enquiry. The implications for pedagogical practices are discussed.